Experimental model of micronodular thymic neoplasm with lymphoid stroma. Issue 4 (16th December 2022) - Niwa, Riko; Hanamatsu, Yuki; Kito, Yusuke; Saigo, Chiemi; Takeuchi, Tamotsu
Abstract: Background: Micronodular thymic neoplasm with lymphoid stroma (MNT), a subtype of thymic tumor, is histopathologically characterized by micronodular thymic epithelial cell nests with lymphoid stroma. Despite the distinct histopathology of MNT, its pathogenesis remains unclear. Methods: In this study, we aimed to examine a thymic tumor harboring thymic epithelial and lymphoid cells in a nonobese diabetic/severe combined immunodeficiency mouse. Results: The excised tumor cells were cultured in vitro and comprised epithelial tumor cells and lymphoid cells. During a three‐dimensional cell culture, the epithelial tumor cells formed micronodular cell nests surrounded by lymphoid stroma. Notably, the lymphoid cells underwent apoptosis when they were separated from the epithelial tumor cells. Cutaneous transplantation of the cultured epithelial cells with splenocytes from BALB/c mice led to tumor formation, and these cells demonstrated a histopathology similar to that of human MNT in a nonobese diabetic/severe combined immunodeficiency mouse. Conclusion: Given its overlapping features with human MNT, the transplanted tumor could serve as an experimental model of this disease. Abstract : Left: Micronodular thymic epithelial cell nests, which exhibited pan‐cytokeratin immunoreactivity by immunohistochemical staining (indicated by arrows) and lymphoid cell stroma (indicated by arrowheads). Right: Micronodular thymic epithelial cell nests and stromal lymphoid cells, indicated by arrows and arrowheads, respectively, was also found in three‐dimensional culture.